INTEGRASI SIG-INFOWORKS RIVER SIMULATION UNTUK PEMODELAN HIDRODINAMIK SUNGAI SADDANG DAN SUNGAI MATA ALLO - Wulandarie, Srie (Jurnal Environmental Science, 2020)
AbstractThe purpose of this study was to determine the hydrodynamic model of the river so that can know the capacity of the river to accommodate the incoming water flow. The simulation models can be used in structural mitigation plan as an attempt to prevent flooding in the future. The application program used to create hydrodynamic models that Infoworks River Simulation integrated with GIS. Data cross-section of the river as much as 39 points inputted into Infoworks River Simulation program. Furthermore, the discharge input the Saddang River and the Mata Allo River to determine variations in water level at each cross-section. The results of this study showed an average increase in water level of the SaddangÂ  and Mata Allo River in the event of the maximum discharge of 2.59 meters. Sectional increased water levels are all cross sections along the Saddang and Mata Allo River Saddang used in modeling the variation of the rise in water level of 0.8 to 5.39 meters.